Environmental economics - Sankar, Ulagnathan (Ed.) (New Delhi Oxford Univeristy Press, 2001)
The book contains classic papers by Hotelling on the economics of exhaustible resources. Sankar's introductory chapter brings into focus the Indian context by analysing the impact of the country's environmental policy regime. International issues are addr
Keywords: Environmental economics; Economics